(untitled) (International Journal of Engineering and Computer Science, 2018)
The general opinion that there is gradual hazardas effect at the cellular level related to human health . The study of the low frequency radio frequency wave reveled that different dimension of EM wave have not shown any DNA damage directly burt there is concern about evidance of cellular effect of EM.The static of very low frequncy EM field lead to biological effect associated with re-distribution of ions. The effects induced by radiofrequency (RF) electromagnetic fields and microwave (MW) radiation in various cellular systems is still increasing. Until now no satisfactory mechanism has been proposed to explain the biological effects of these fields.this study is to investigate effect of MW radiation on cell proliferation.